Faktor Yang Mempengaruhi Pembelian Obat Malaria Di Warung - Muhamad Nizar; Yulian Taviv; Terang Uli Sembiring; Lukman Hakim (ASPIRATOR - Journal of Vector-borne Disease Studies, 2013)
About 80% of Indonesia populations lived in malaria endemic areas. AMI reported to date is still high, on the other side of the MDG targets is to reduce AMI (< 5/1000 populations in 2015), while the elimination of malaria in Sumatra is expected on 2020. According to Riskesdas 2007, the malaria suspected who utilizing health services is remains low (<2%), whereas people who utilizing the general health care facilities is 48.7%. The study has been conducted to analyze the factors that influence the use of malaria drugs purchased in the stall. This study was using a quantitative approach. The chi-square and logistic regression test was used to analyzed the independent variables (age, sex, duration of illness, work, and education level) against variable dependent (purchasing of malaria drugs in the stall). A cross-sectional study was done with inclusive criterias: fever >38 ° C, chills, cold sweating, headache, and muscle pain or splenomegaly at 4 health centers in January to April 2011. Interview was assigned to 220 respondents; 53.2% of respondents aged over 40 years, predominantly female (52.7%). In general, respondents have a job (66.4%) with low educational level (81.8%), and 67.7% get a pain less than 4 days. Results shows that occupation factor is significantly related to drug purchasing behavior (p = 0.003). Model of risk factors that influencing malaria drug purchases in the stall is the kind of work that is influenced by the low education level (p-value = 0.003) with odds ratio is 15.5%.